The role of afforestation species as a driver of Hg accumulation in organic horizons of forest soils from a Mediterranean mountain area in SW Europe - Méndez-López, Melissa (2022)
Forest areas are a primary sink of atmospheric mercury (Hg) within terrestrial ecosystems, whereas forest vegetation plays a key role in atmospheric Hg transfer to soil horizons. This study assessed variations in total Hg contents (HgT) and accumulation (HgRes) in the soil organic horizons of a forest area in NE Portugal, where post-wildfire afforestation led to the substitution of the native deciduous species (Quercus pyrenaica) by fast-growing coniferous species (Pseudotsuga menziesii and Pinus nigra). The study also evaluated, for each species, the links between Hg contents and other biophilic elements of soil organic matter (C, N, S) present in organic subhorizons (OL, OF, OH). Mean HgT in the organic horizons of the different tree species follow the sequence: P. nigra (88 μg kg−1) < Q. pyrenaica (101 μg kg−1) < P. menziesii (141 μg kg−1). The highest HgRes for the entire organic horizon was found under P. menziesii (471 μg m−2), followed by P. nigra (253 μg m−2) and Q. pyrenaica (189 μg m−2). Among the organic subhorizons, values of HgT and HgRes follow the sequence OL < OF < OH, which is consistent with the degree of organic matter humification. Indeed, HgT and HgRes correlated significantly with the C/N and C/S ratios for all species and organic subhorizons, suggesting that the quality of organic matter may influence strongly the Hg fate in these forest soils. Soils from P. menziesii plots have shown an HgRes 2.5 times higher than in plots dominated by the native Q. pyrenaica. Hg accumulation in the organic horizons, promoted in the coniferous species, may increase the risk of Hg mobilization due to wildfires and forest management practices. Therefore, forest management plans should select cautiously the tree species for afforestation in order to minimize adverse environmental effects caused by changes in the biogeochemical cycle of contaminants such as Hg.